#TITLE_ALTERNATIVE# - (NIM 23206327), HENDRAYANA
Interactive simulation of nature phenomenon bases on physics has become one active research areas in computer science and computer graphic. Method smoothed particle hydrodynamics has many applied for fluid modelling. This method is interpolation from particle system for modeling fluids in nature phenomenon like smoke, river flow, lava flow, floods even tsunami. In this research will be studied about design and implementation of fluid with method smoothed particle hydrodynamics on interactive flood simutation and the interaction with object. Research started from election of method to model fluid so implementation of interaction of fluid with object. This research also studies about optimization of seeking technique of nearest neighbour in smoothed particle hydrodynamics applies method staggered grid. New seeking technique efficient to look for prediction plane of collision detection between fluid based particles and terrain. Based on system implementation of axis sequence X-Z-Y is which most effective for seeking of nearest neighbour applies using staggered grid data structure. With only increasing the velocity and emitter rate of particle, the simulation of river flow would at once turns into floods.